THE STUDY OF ECONOMIC MECHANISMS OF TRANSPORT MANAGEMENT ABROAD - Shvets, S. I.; Zhuravel, V. V. (Science and Transport Progress, 2009)
The economic mechanism of railway transport management in the most developed countries of the world is investigated.